Japanese Colonialism Since The 19th Century - Fatonah, Fatonah; Gusmahansyah, Risatri; Defrianti, Denny; Yanfaunnas, Yanfaunnas; Hasan, Uswan (LPPM Universitas PGRI Sumatera Barat, 2024)
This research will focus on studying the history of East Asia, how Japan became a colonial state since the 19th century. The intent and purpose of this research is to find out how the history of Japan's journey to becoming a colonialist country since the 19th century and becoming a very influential country. The method used by the author in this study is the historical research method which is divided into four stages, namely heuristics (collecting reference sources either books, journals, or articles from various sources related to the research theme) source criticism, interpretation (reinterpreting facts found), and historiography (writing the results obtained from this study). This is motivated by the emergence of imperialism which made several other countries form a colonial state. One of the countries in East Asia that adheres to imperialism is Japan, which in the end Japan became one of the countries with major influence in Asia including In Indonesia.